Impact of Classroom Management on Academic Achievement of Students' in Oral English in Afijio Local Government Area, Oyo State: Implications for Sustainable Development - Enu, E. N.; Olusoji, I. O.; Awolere, O. O.; Awolere, O. O.; Dahunsi, O. J.; Badmus, O. M.; Aimasiko, O. G. (Emmanuel Alayande University of Education Journal of Multidisciplinary Studies (EAUED-JMS), 2025)
This study examines the impact of classroom management on academic achievement and behavioral outcomes in public senior secondary schools in Afijio Local Government Area, Oyo State, and explores its broader implications for sustainable development. Effective classroom management is fundamental to creating a stable, inclusive, and productive learning environment, which in turn promotes quality education one of the core pillars of sustainable development. Using a mixed-methods approach involving questionnaires, interviews, and direct classroom observations, the study identifies key management practices such as rule enforcement, time management, student engagement, and teacher-student relationships. Results indicate that schools with strong classroom management strategies show improved student performance, reduced disciplinary issues, and enhanced school climate. These outcomes contribute to the development of responsible, educated individuals capable of supporting local and national development goals. The study concludes that investing in teacher capacity for classroom management is vital for achieving long-term educational and developmental outcomes in Afijio and beyond.